T‐cell tracking using Cerenkov and radioluminescence imaging. Issue 10 (5th July 2018) - Boschi, Federico; De Sanctis, Francesco; Ugel, Stefano; Spinelli, Antonello E.
Abstract : Cancer immunotherapy is a promising strategy based on the ability of the immune system to kill selected cells. In the development of an effective T‐cell therapy, the noninvasive cell tracking methods play a crucial role. Here, we investigate the potentialities of T‐cell marked with radionuclides in order to detect their localization with imaging techniques in small animal rodents. A protocol to label T‐cells with 32 P‐ATP was tested and evaluated. The homing of 32 P‐ATP labeled T lymphocytes was investigated by Cerenkov luminescence imaging (CLI) and radioluminescence imaging (RLI). The first approach relies on the acquisition of Cerenkov photons produced by the beta particles emitted by the 32 P internalized by lymphocytes; the second one on the detection of photons coming from the conversion of radioactive energy in light done by scintillator crystals layered on the animals. The results show that T‐cell biodistribution can be optically observed by both CLI and RLI in small animal rodents in in vivo and ex vivo acquisitions. T‐cell localization in the tumor mass was definitively confirmed by flow cytometry. Abstract : Immunotherapy represents a promising strategy against cancer. Since cytotoxic T lymphocyte (CTL) infiltration in solid tumor correlates with better survival in cancer patients, here we propose a new method allowing the non‐invasive tracking of adoptively transferred lymphocytes. We show that 32 P‐ATP‐labeled CTLs can be imaged by Cerenkov or radio luminescence‐based optical techniques in mice. Moreover, 32 P‐ATP‐labeling can combine the cytotoxic properties of CTLs with the radiation damages produced by 32 P.